The effect of firm and country characteristics on mandatory disclosure compliance - Lucas, S. M. R.; Lourenço, I. C. (International Journal of Managerial and Financial Accounting, 2014)
Our study investigates the role of firm and country characteristics in determining the level of compliance with mandatory disclosure requirements. We also examine whether the role of firm characteristics hold across different country environments. Our empirical study relies on European Union listed firms included on the STOXX Europe 600 Index and on their level of compliance with IFRS 3, Business Combinations disclosure requirements. Our results demonstrate that both firm and country characteristics develop a significant task in explaining the level of compliance with mandatory disclosure requirements. They confirm that firms located in a common-law country have the strongest, and firms located in a French-civil-law country the weakest, level of compliance with IFRS 3 disclosure requirements, with firms located in a Scandinavian- and German-civil-law country placed in the middle. Our findings also suggest that return on assets is the main determinant of the level of compliance with IFRS 3 disclosure requirements in the group of common-law plus Scandinavian- and German-civil-law countries, while leverage is the main determinant in the group of French-civil-law countries